Induction of systemic resistance through calcium signaling in Arabidopsis exposed to air plasma-generated dinitrogen pentoxide - Shota Sasaki; Hiroto Iwamoto; Keisuke Takashima; Masatsugu Toyota; Atsushi Higashitani; Toshiro Kaneko (PLoS ONE, 2025)
Plasma technology, which can instantaneously transform air molecules into reactive species stimulating plants, potentially contributes to developing a sustainable agricultural system with high productivity and low environmental impact. In fact, plant immunity activation by exposure to a reactive gas mainly consisting of dinitrogen pentoxide (N2O5) was recently discovered, while physiological responses to N2O5 are rarely known. Here, we demonstrate early (within 10 min) physiological responses to N2O5 gas in Arabidopsis. Exposure to N2O5 gas induced an increase in cytosolic Ca2+ concentration within seconds in directly exposed leaves, followed by systemic long-distance Ca2+-based signaling within tens of seconds. In addition, jasmonic acid (JA)-related gene expression was induced within 10 minutes, and a significant upregulation of the defense-related gene PDF1.2 was observed after 1 day of exposure to N2O5 gas. These systemic resistant responses to N2O5 were found unique among air-plasma-generated species such as ozone (O3) and nitric oxide (NO)/nitrogen dioxide (NO2). Our results provide new insights into understanding of plant physiological responses to air-derived reactive species, in addition to facilitating the development of plasma applications in agriculture.